2009
DOI: 10.1245/s10434-009-0398-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Rectal Resection for Cancer: Effects of Conversion on Short-Term Outcome and Survival

Abstract: Our study suggests that conversion to open surgery does not affect postoperative outcome, but could have a negative impact on long-term overall recurrence rate. LRR should be performed by experienced surgeons in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 35 publications
8
96
2
1
Order By: Relevance
“…The hospital stay was prolonged in the CONV group (colon cancer patients: 8 vs 7 days; rectal cancer patients: 10 vs 8 days), consistent with the results reported in the literature, although these differences did not reach statistical significance. In nonrandomized comparative and descriptive studies, conversion also is associated with worse oncologic outcomes in terms of higher local recurrence and reduced survival rates [13,16,18,20,21,23]. However, the cited studies present several shortcomings including small sample sizes, short follow-up periods, and lack of adequate statistical analysis that limit the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hospital stay was prolonged in the CONV group (colon cancer patients: 8 vs 7 days; rectal cancer patients: 10 vs 8 days), consistent with the results reported in the literature, although these differences did not reach statistical significance. In nonrandomized comparative and descriptive studies, conversion also is associated with worse oncologic outcomes in terms of higher local recurrence and reduced survival rates [13,16,18,20,21,23]. However, the cited studies present several shortcomings including small sample sizes, short follow-up periods, and lack of adequate statistical analysis that limit the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported higher morbidity and mortality rates and a longer postoperative hospital stay [3,[13][14][15][16][17][18], whereas others did not find significant differences in comparisons with to non converted patients [12,[19][20][21][22]. The oncologic outcomes for converted patients are poorly investigated, and the data currently available are unclear [10,[12][13][14][15][16][17][18][19][20][21][22][23]. This study aimed to evaluate the impact of conversion to open surgery on short-and long-term outcomes in a large series of patients undergoing laparoscopic resection for nonmetastatic colorectal cancer.…”
mentioning
confidence: 99%
“…Regarding the small number of patients undergoing IA after SIL-RH, no conclusion could be reached regarding the most appropriate type of anastomosis after SIL-RH. Conversion of a laparoscopic procedure is associated with increased postoperative morbidity [43] as well as LOS [44], compared with planned open procedures. Vettoretto et al [45] in their meta-analysis found no statistically significant difference in the conversion rate between SIL-RH and ML-RH patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a classic trial, laparoscopic surgery was associated with increased CRM positivity rates compared with open surgery (12.4% vs. 6.3%). Laparoscopic rectal cancer surgery in particular is associated with a higher conversion rate when compared with colonic laparoscopic resection, and those that are converted to open surgery have a higher mortality rate [5,11] . This is a possible reflection of the technical challenges that confront a surgeon during rectal dissection.…”
Section: Questionable Safety Of Laparoscopic Rectal Dissectionmentioning
confidence: 99%